Meningkatkan Pencegahan Insiden Motor Vehicle Crash (MVC) dengan Inovasi TASBE PaDaGeSiT di PT. XYZ - Sugiono, Nana; Andivas, Marulan; Primadani, Joshua (Fakultas Teknik UMRI, 2026)
This study aims to enhance Motor Vehicle Crash (MVC) prevention efforts in PT. XYZ's operational activities through the implementation of the TASBE PaDaGeSiT innovation. The study was conducted to address the persistently high potential risk of MVC despite the company's achievement of zero incidents in the Motor Vehicle Safety (MVS) aspect. Problem identification and analysis were carried out using fishbone diagrams, Pareto analysis, and Failure Mode and Effect Analysis (FMEA) to determine root causes and prioritize risks requiring control measures. Based on the analysis results, the TASBE innovation, founded on the Plan-Do-Check-Action (PDCA) cycle and strengthened by the PaDaGeSiT behavioral approach, was implemented. The implementation results demonstrated a reduction of more than 50% in Risk Priority Number (RPN) values for major risk factors and an overall risk reduction of 89.8%, resulting in a more controlled risk distribution. These findings indicate that the TASBE PaDaGeSiT innovation is effective in strengthening the MVC prevention system, improving road safety risk control, and supporting the sustainability of the company's zero-incident achievement.